2021
DOI: 10.3390/ijerph18147437
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Work Environment and Perceived Stress among Seniors with Physically Demanding Jobs: The SeniorWorkingLife Study

Abstract: Background: Poor psychosocial work conditions are known to foster negative health consequences. While the existing literature on this topic focus mainly on white-collar workers, the influence of different aspects of the psychosocial work environment in physically demanding jobs remain understudied. Likewise, senior workers represent a population of the workforce at increased risk of adverse health outcomes and premature exit from the labour market. This study investigates the association between psychosocial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
(69 reference statements)
0
3
0
1
Order By: Relevance
“…For example, it can be possible to perform physically demanding tasks in a more comfortable and more adapted way to one's physical conditions. In a similar vein, one recent cross-sectional study including mostly blue-collar workers above 50 years of age, who all had heavy physical demands, found that low job resources were associated with higher perceived stress ( Vinstrup et al, 2021 ). However, stratifying by gender, we found that the buffering effect of decision authority only remained significant for men.…”
Section: Discussionmentioning
confidence: 90%
“…For example, it can be possible to perform physically demanding tasks in a more comfortable and more adapted way to one's physical conditions. In a similar vein, one recent cross-sectional study including mostly blue-collar workers above 50 years of age, who all had heavy physical demands, found that low job resources were associated with higher perceived stress ( Vinstrup et al, 2021 ). However, stratifying by gender, we found that the buffering effect of decision authority only remained significant for men.…”
Section: Discussionmentioning
confidence: 90%
“…A study that investigated associations between occupational stressors and perceived stress in elderly people in Denmark, with physically demanding jobs, showed that the lower the level of control over work and social support from co-workers, the greater the level of stress ( 41 ) . Research with motorcyclists in Indonesia identified that social support from family, friends or other sources reduced the stress of riding the motorcycle and the worker’s concerns, as well as favoring harmonious relationships ( 42 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudo que investigou associações entre estressores ocupacionais e estresse percebido em idosos da Dinamarca, com empregos fisicamente exigentes, mostrou que, quanto menor o nível de controle sobre o trabalho e de suporte social dos colegas de trabalho, maior foi o nível de estresse (41) . Investigação com motociclistas da Indonésia identificou que o suporte social da família, amigos ou outras fontes reduziu o estresse na condução da motocicleta e as preocupações do trabalhador bem como favoreceu relacionamentos harmoniosos (42) .…”
Section: Estresse Percebido Por Mototaxistas E Sua Relação Com Caract...unclassified